Effect of curing temperature on mechanical strength, hydrophobicity, chemical and thermal stability of Cardanol‐derived Resol‐polyurethane films/coatings. Issue 7 (7th May 2022) - Shaily,; Zafar, Fahmina; Jahan, Afroz; Parveen, Bushra; Sharmin, Eram; Alam, Manawwer; Nishat, Nahid
Abstract: The utilization of renewable resources has increased over the last few years in different fields due to environmental and economic concerns. Cashew nut shell liquid (CNSL) is cheaper, abundantly available, and an eco‐friendly agro‐waste product, which holds the potential to significantly replace petro‐based phenols. Present work focusses on the preparation of (i) Cardanol‐based polyols (resol) in different ratios [Cardanol: formaldehyde 1:1.2(Rol1 ), 1:1.6 (Rol2 ), and 1:2.0 (Rol3 )], (ii) their polyurethanes, and (iii) freestanding, transparent, flexible and thin films/coatings obtained through "Green" route. The effect of curing temperature on the overall performance of films/coatings has also been investigated. The films/coatings obtained by baking at 80 ± 5°C (BK‐Rol1/2 ‐PU) exhibited improved physicomechanical performance compared with films/coatings obtained at room temperature (RT‐Rol1/2 ‐PU). BK‐Rol1/2 ‐PU and RT‐Rol1/2 ‐PU demonstrated excellent chemical stability. XRD revealed that both BK‐Rol2 ‐PU and RT‐Rol1/2 ‐PU films were amorphous and TGA confirmed that BK‐Rol2 ‐PU showed higher thermal stability compared with RT‐Rol2 ‐PU films. The contact angle measurements indicated a higher hydrophobic character of BK‐Rol1/2 ‐PU (96°) relative to RT‐Rol1/2 ‐PU (90°). These polyurethane films/coatings can be used for protective and decorative purposes. As BK‐Rol1/2 ‐PU films/coatings outperformed RT‐Rol1/2 ‐PU, the overall results confirmed that curing temperature had a remarkable effect on the performance characteristics of coatings/films. Abstract : Cardanol based resol polyurethane (Rol‐PU) synthesized in order to the comparative study of room temperature (RT) and baked (BK) films/coatings (80‐100oC). BK films/coatings show better thermal stability (upto 210‐225 °C), mechanical/chemical resistivity, bio‐degradability, hydrophobicity (C.A., 96°), and flexibility which can be utilized in protective, anticorrosive, and decorative coating materials.